TINGKAT KEHARMONISAN KELUARGA PADA MAHASISWA PEKERJA - Hani Rosyidah; Ipung Hananto; Sri Ayatina Hayati (Pamomong: Journal of Islamic Educational Counseling, 2023)
Family harmony is key in ensuring family resilience from both social and psychological perspectives. It is a highly influential concept in shaping a child's character and facilitating the positive development of their personality. This research aims to determine the level of family harmony among working students. The research utilized a survey with a quantitative approach involving 85 working students. Data collection was done using the family harmony scale developed by Kavikondala et al. (2016), which identifies five dimensions of family harmony: communication, conflict resolution, patience, family identity, and quality time. This research indicates that working students have a moderate level of family harmony. This study serves as a basis for enhancing family harmony within the scope of Guidance and Counseling.